The Implementation of REST API in Multi-Platform Software Development for Food and Beverage Learning Application - Randy Ramadhan; Yuda Syahidin (Politeknik Piksi Ganesha Indonesia, 2022)
This website-based food and beverage learning application is an educational application about food and drink. The problem was that information was more often accessed on smartphone devices, such as Android. The research method used was quantitative, so this research provides a concrete value for the optimal implementation of the REST API. The result obtained was that the website-based REST API application worked on multi-platform devices. With the implementation of this REST API, various devices can communicate with each other with the same source and data, so it does not cause multiple databases to store information.